Agronomic evaluation of rice (Oryza sativa) genotypes under varying fertility levels - BAHUGUNA, ANJALI; SINGH, D K; SUPRIYA; KUMAR, AMIT; GARG, KAMAL; VERMA, PARKASH; PATEL, SHASHANK; S, SUDARSHAN (The Indian Journal of Agricultural Sciences, 2023)
The study suggests that rice varieties IET-27263 and NDR-359 can achieve increased yields by employing 150% of the recommended fertilizer dose (180:90:60 kg NPK/ha). Using 150% of the suggested nitrogen dose (RDN) results in notably elevated gross and net returns, as well as an improved benefit-to-cost ratio (B: C). Particularly, genotype IET-27263 exhibits significantly superior gross return, net return, and B: C ratio compared to other genotypes.